2018
DOI: 10.4028/www.scientific.net/kem.782.268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Calcium Hydroxide from Indonesian Limestone as Endodontic Intracanal Medicament

Abstract: Calcium hydroxide [Ca (OH)2] has been the gold standard for endodontic medicament as inter-appointment dressing, due to its ability to act as antimicrobial agent and to promote hard tissue healing. The main mechanism of this material is the release of Ca2+ and OH- ions through its vehicle, providing high alkaline pH. Indonesia, has many potential resources, namely limestone (CaCO3), that can be utilized as raw material for Ca (OH)2. The objective of this present study is to investigate the synthesis and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…SP88857105, USA) for 1 h at a speed of 300 rpm, 50 °C. The Ca(OH) 2 paste was dried at 120 °C, then crushed using a mortar and pestle and sieved using 400 mesh to obtain a powder of Ca(OH) 2 Palimanan (CaP) [ 17 ]. The fine particle of Ca(OH) 2 powder was obtained by beads milling the CaP powder for 4 h with different active agents and medium in each group ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SP88857105, USA) for 1 h at a speed of 300 rpm, 50 °C. The Ca(OH) 2 paste was dried at 120 °C, then crushed using a mortar and pestle and sieved using 400 mesh to obtain a powder of Ca(OH) 2 Palimanan (CaP) [ 17 ]. The fine particle of Ca(OH) 2 powder was obtained by beads milling the CaP powder for 4 h with different active agents and medium in each group ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ca(OH) 2 transforms to CaCO 3 when in contact with air, and this carbonation process increases as environmental humidity rises [ 15 , 16 ]. Our previous study successfully synthesized Ca(OH) 2 from natural limestone in Palimanan area in West Java, Indonesia [ 17 ]. This Palimanan Ca(OH) 2 (CaP), was further optimized by reducing its particle size through a wet beads milling process.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, limestone can be utilized in the medical field, such as material research for clinical applications and its development in the manufacture of materials to increase the economic value of limestone itself. 8, 9 The Palimanan limestone has been successfully synthesized and characterized by our previous study, however improvement and in vitro evaluations regarding its physical/mechanical properties is yet to be carried out. Ca(OH) 2 can be applied as inter appointment dressing, as well as pulp capping agent, therefore, additional material such as retarders, accelerators, radiopacifier or modification on its particle size must be adjusted according to its clinical application needs.…”
Section: Ca(oh)mentioning
confidence: 99%
“…The basic mechanism of a spectrophotometer is the light absorption as a beer-lambert law which states that when a beam of light is passed through a transparent cell containing a solution will be absorbed. 9 A spectrophotometer runs by using a solution and measure the absorbance at the right wavelength. The selected wavelength is usually the maximum absorption wavelength (λmax), if there is a small error in setting the wavelength scale then there is an effect on the absorbance measurement.…”
Section: Ca(oh)mentioning
confidence: 99%
“…[ 13 ] There has been no similar study reported to date for calcium hydroxide nanoparticles synthesized by the chemical precipitation route. Thus, calcium hydroxide is also used as an endodontic intra‐canal medicament [ 14 ] and in endodontic treatment. [ 15 ] There are numerous pH formulations reported for calcium hydroxide with chlorhexidine digluconate.…”
Section: Introductionmentioning
confidence: 99%